Investigation of pH measurement of drinking water by disposable, high accuracy, and semi-transparent BN/Ag nanocomposite thin film sensors. Issue 2 (1st February 2023) - Mohammadigharehbagh, Reza; Pat, Suat; Akkurt, Nihan; Korkmaz, Şadan
Abstract: A pH measurement of water by disposable, high accuracy, and semi-transparent BN/Ag nanocomposite thin film sensors manufactured by thermionic vacuum arc technique have been investigated. According to the results, columnar, crack-free, well connection among oriented grains and dense particles were growth on the BN/Ag electrode coatings. It is evident from the electrochemical impedance spectroscopy, ohmic resistance, R value is pH-sensitive, and it was increased by decreasing pH. As a results, disposable and high accuracy BN/Ag nanocomposite thin film sensors have been very good worked between pH 6.64 and pH 7.83. This range is very good fit the range of pH values of the body liquids and drinking water. And, manufactured sensor worked in the range with high accuracy. Graphical Abstract: UF0001